Optimizing Teacher Performance Through The Implementation Of Progressive Work Culture And Dynamic Leadership Styles - Rahmamulyati, Asde; Handoko, Yunus; Murtianingsih, Murtianingsih (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
Education in schools cannot be separated from learning. Learning is designed in such a way that the material provided by the teacher reaches the students. In its application, some teachers have shown a lot of good performance, developing their skills to carry out their duties and functions as educators. However, at SDN 138 Pekanbaru Riau, the performance of teachers has not had optimal performance. This study aims to examine the influence of work culture, leadership style and work motivation on the performance of SDN 138 Pekanbaru teachers. This study used quantitative methods. Sampling using the nonprobability sampling method, with a saturated sensus, where all members of the population are sampled. The sample or respondents in this study amounted to 31 teachers. Data collection method using questionnaire. Data analysis uses data quality tests, classical assumption tests, multiple linear regression and hypothesis testing, namely coefficients of determination, t tests, and f test. The results of the research partially and simultaneously concluded that work culture, leadership style and work motivation have a significant effect on teacher performance.